Serotonin rebalances cortical tuning and behavior linked to autism symptoms in 15q11-13 CNV mice - Nakai, Nobuhiro; Watanabe, Yasuhito (Science advances, 2017)
Serotonin is a critical modulator of cortical function, and its metabolism is defective in autism spectrum disorder (ASD) brain. How serotonin metabolism regulates cortical physiology and contributes to the pathological and behavioral symptoms of ASD remains unknown. We show that normal serotonin levels are essential for the maintenance of neocortical excitation/inhibition balance, correct sensory stimulus tuning, and social behavior. Conversely, low serotonin levels in 15q dup mice (a model for ASD with the human 15q11-13 duplication) result in impairment of the same phenotypes. Restoration of normal serotonin levels in 15q dup mice revealed the reversibility of a subset of ASD-related symptoms in the adult. These findings suggest that serotonin may have therapeutic potential for discrete ASD symptoms. Serotonin enhancement during developmental stages restores autism symptoms in a mouse model of human 15q11-13 duplication. Serotonin enhancement during developmental stages restores autism symptoms in a mouse model of human 15q11-13 duplication.